2016
DOI: 10.1063/1.4960598
|View full text |Cite
|
Sign up to set email alerts
|

Fast-ion Dα spectrum diagnostic in the EAST

Abstract: In toroidal magnetic fusion devices, fast-ion D-alpha diagnostic (FIDA) is a powerful method to study the fast-ion feature. The fast-ion characteristics can be inferred from the Doppler shifted spectrum of D light according to charge exchange recombination process between fast ions and probe beam. Since conceptual design presented in the last HTPD conference, significant progress has been made to apply FIDA systems on the Experimental Advanced Superconducting Tokamak (EAST). Both co-current and counter-current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that reconstructing the velocity distribution function from a diagnostic system with incomplete coverage of velocity space is a challenging task [7,11,[14][15][16]. Specifically at the EAST tokamak, the two-view FIDA diagnostic [17,18] is sensitive to fast ions in substantial regions of velocity space, but leave other regions covered by only one view [19]. To nevertheless enable reliable reconstructions of the fast-ion distribution from sparse datasets, a palette of prior information has been developed [14,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that reconstructing the velocity distribution function from a diagnostic system with incomplete coverage of velocity space is a challenging task [7,11,[14][15][16]. Specifically at the EAST tokamak, the two-view FIDA diagnostic [17,18] is sensitive to fast ions in substantial regions of velocity space, but leave other regions covered by only one view [19]. To nevertheless enable reliable reconstructions of the fast-ion distribution from sparse datasets, a palette of prior information has been developed [14,15,20].…”
Section: Introductionmentioning
confidence: 99%
“…1. The FIDA diagnostic layout on EAST.aaa spectral resolution and high temporal resolution, respectively, high resolution spectrometers are equipped with both FLP200 and HoleSpec spectrometers, 11 and fast filter-based photomultiplier systems including the array-PMT and single-PMT have been both available for the complementary measurements.…”
Section: Fida Diagnostic Layoutmentioning
confidence: 99%
“…Then it has been applied on many magnetic devices. [3][4][5][6][7][8][9][10] To investigate the behavior of fast ions on EAST (Experimental Advanced Superconducting Tokamak), a FIDA diagnostic system with a spectrometer (s-FIDA) 11 was mounted since 2014 which is mainly used to analyze the different energy components of fast ions. In order to study the interaction between instabilities and fast-ion transport, recently the FIDA system was extended by using a combination of a bandpass filter and a photomultiplier tube (PMT) (f-FIDA), which was first commissioned on NSTX 3 and also applied on DIII-D, 4 and it will provide the temporal evolution of the blue shifted component of the Doppler shifted spectrum by integrating the Note: Paper published as part of the Proceedings of the 22nd Topical Conference on High-Temperature Plasma Diagnostics, San Diego, California, April 2018. a) Author to whom correspondence should be addressed: changjiaf@ipp.ac.cn desired spectral band from 651 nm to 654 nm before detection by the PMT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIDA can be characterised as charge exchange recombination spectroscopy (CXRS) applied to investigate the distribution function of confined fast ions. The technique relies on measuring the Doppler shifted Balmer alpha emission from charge exchange (CX) reactions between fast hydrogenic ions and donor neutrals 3 , with systems installed on multiple fusion devices [4][5][6][7][8][9][10] . The large Doppler shift of the radiation of neutralised energetic particles separates their emission from other Balmer-alpha contributions such as the beam and halo emission and makes the measurement of the typically weak fast-ion emission possible.…”
Section: Introductionmentioning
confidence: 99%